Barrows in the Skirts of the Forest: Excavation of a Wielbark culture cemetery at Mirosław 37, Ujście commune, Piła district, Greater Poland Voivodeship - Michałowski, Andrzej (Faculty of Archaeology, Adam Mickiewicz University in Poznań, 2021)
Archaeological excavations carried out at site 37 in Mirosław since 2016 have revealed a barrow cemetery of the Wielbark culture. An enormous amount of data hitherto collected has greatly facilitated better understandings of the settlement patterns of the population represented by this cultural group in the northern part of Greater Poland. This information provides a truly compelling and valuable contribution into the study of the burial customs of communities inhabiting northern Greater Poland during the Roman Iron Age period. As a result of this work, two of seven preserved mounds were examined. These contained two female burials: an inhumation burial, dated to phase B2/C1 deposited in Barrow 7 and a cremation burial dated to phase C1a deposited in Barrow 1. Also, other objects were recorded in the area of the mounds, in particular traces that are evidence of metallurgical production. What is more, a fragment of the plane part of the site was identified using non-invasive research methods – magnetometer prospection. A part of this area was examined by means of excavation, which confirmed the occurrence of both burial goods (a burial that was first exhumed in antiquity, was possibly made from another, leveled burial mound) as well as other objects, present in the cemetery and related to the funeral activities. Additionally, the zone between Barrows 6 and 7 yielded the burial of a small child. The excavations have stimulated numerous research questions which have not yet been satisfactorily answered and are vital for describing the structure of the cemetery and providing its full chronology.
Keywords: Wielbark culture; barrows; burial custom; bloomeries; proglacial stream valley of the Noteć River